2014
DOI: 10.1093/ehjci/jeu091
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of primary mitral regurgitation using left ventricular volumes: a three-dimensional transthoracic echocardiographic pilot study

Abstract: RF can be routinely determined using 3D LV volumes with a high feasibility in patients with primary MR and is reliable for identification of Grade 3+ or Grade 4+ MR. The incorporation of this parameter into the currently recommended multiparametric integrative approach might be helpful to discriminate significant MR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Therefore, novel technics, such as field optimization method (FOM) automatically calculates the location of orifice area on research for eliminating these pitfalls ( 8 ). Recent studies have demonstrated that 3-D PISA method is superior to 2-D PISA method ( 9 , 10 ). This study is the first to consider apical flow dynamics in LV as a perspective to assess MR severity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, novel technics, such as field optimization method (FOM) automatically calculates the location of orifice area on research for eliminating these pitfalls ( 8 ). Recent studies have demonstrated that 3-D PISA method is superior to 2-D PISA method ( 9 , 10 ). This study is the first to consider apical flow dynamics in LV as a perspective to assess MR severity.…”
Section: Discussionmentioning
confidence: 99%
“…10 3D echocardiography full-volume datasets of the LV were obtained in an adjustable volume divided into six sub-volumes. 1 LV forward stroke volume was calculated as the product of LV outflow tract velocity-time integral (VTI) by LV outflow tract crosssectional area. Mitral 2D-and 3D-MRF (2D Echo MRF and 3D Echo MRF) were obtained off-line (EchoPAC workstation (BT12, General Electric Healthcare)) by measuring the difference in LV total stroke volume (obtained from either 2D or 3D acquisition) and aortic forward stroke volume normalized to LV total stroke volume, by a third investigator, blinded to MR grading of the 2 experts and without access to echocardiography -Doppler data used for the integrative multiparametric approach.…”
Section: Methodsmentioning
confidence: 99%
“…40 46 For the RF parameter, each of the components (TSV, FSV or RV) has intrinsic error, because multiple measures are combined into each of these volume components, and the error increases when the volumes are subtracted. 27 In figure 4 and table 1 (Patient 9), we show how echocardiographic volumetric measurement variability 47 of RF may shift a patient from proportionate (RV/ LVEDV=0.14 at RF=50% and EF=30%) towards a disproportionate profile (RV/LVEDV=0.23 and RF=59% and EF=39%), assuming the proposed RV/LVEDV cut-off being 0.20 12 and/or RF >50%. 13 Indeed, apart from biological variability, the SD for the patients in the conceptual framework ('their position in the EROA/LVEDV and RV/LVEDV graphs') when measured with the volumetric method is determined by echocardiographic measurement variability of LVEDV, LVESV (EF), FSV (RF) and TVI, which may be substantial.…”
Section: Echocardiographic Assessment Of Rfmentioning
confidence: 97%
“…13 Indeed, apart from biological variability, the SD for the patients in the conceptual framework ('their position in the EROA/LVEDV and RV/LVEDV graphs') when measured with the volumetric method is determined by echocardiographic measurement variability of LVEDV, LVESV (EF), FSV (RF) and TVI, which may be substantial. 27 47 Therefore, additional imaging such as 3D echocardiography 47 or CMR may be considered 44…”
Section: Echocardiographic Assessment Of Rfmentioning
confidence: 99%